A practical guide to medical ethics for intensivists. (February 2019) - Innes, Richard; Montgomery, Hugh; Bolton, Jim; Rowland, Matthew; Hannam, Andrew; Lindsay, Simon; Sankey, Paul
This series of articles provides a practical guide to dealing with the complex ethical and legal challenges we face in the provision of Intensive Care. They explain the implications of recent legal rulings and cases (such as "Montgomery" and the tragic case of Charlie Gard), and include discussion of clinical scenarios with which we are all familiar. Each article is written by those who are not only experts in their fields, but who also deal with these issues on a day-to-day basis.